Toward Filipino Self-Determination: Beyond Transnational Globalization - Viola, Michael (Kasarinlan: Philippine Journal of Third World Studies; Vol 24 No 1-2 (2009): The Philippines in the WTO, 2011)
In his latest book Toward Filipino Self-Determination: Beyond Transnational Globalization, Epifanio San Juan, Jr. uncovers the concealed operations of power and the historic inequalities of political economic systems that have impacted Filipinos in an age of globalized crisis and contradiction. While the definition of globalization is often debated, for the majority of people in the Philippines, the process of globalization can be more accurately described as “gobble-ization” (McLaren and Farahmandpur 2001). Similar to the mass destruction in the Philippines caused by Typhoon Ondoy, the mechanisms of corporate globalization have enabled an international ruling class to pillage the resources of the islands, leaving behind an entire population submerged in the overflows of structural adjustment, debt, and privatization. The rule of the high water is the doctrine of neoliberalism where every layer of the nation’s social fabric is a site of looting, as the market has become the organizing logic of an entire social sphere. San Juan’s book is an important contribution to the fields of globalization, race, and postcolonial studies as he foregrounds the domains of transformative possibility within culture and social life for Filipinos in a global diaspora, a population that has historically been greatly impacted by the tides of capitalist production.